A STUDY OF TEACHER’S REACTION TO THE STUDENT’S RESPONSES IN TERM OF INITIATING TALK IN THE SPEAKING CLASS AT THE JUNIOR HIGH SCHOOL (RETAIN, 2014)
A STUDY OF TEACHER’S REACTION TO THE STUDENT’S RESPONSES IN TERM OF INITIATING TALK IN THE SPEAKING CLASS AT THE JUNIOR HIGH SCHOOL NORISMA ALIF FUJIYANTI English Education, Language and Art Faculty, State University of Surabaya hazuke.fuji@yahoo.com AHMAD MUNIR English Education, Language and Art Faculty, State University of Surabaya munstkip@yahoo.com Abstrak Penelitian ini merupakan penelitian deskriptif kualitatif tentang reaksi guru yang berfokus pada reaksi guru terhadap respon siswa dan fitur konstruksi atau obstruksi bahasa guru. Penelitian ini bertujuan untuk mendeskripsikan reaksi guru terhadap respon siswa dan mengklasifikasikannya ke dalam 14 fitur bahasa guru berdasarkan Walsh (2006). Subyek penelitian ini adalah guru bahasa Inggris perempuan dan siswa kelas tujuh dari SMP At- Taqwa Surabaya. Data utama diambil dari pengamatan. Rekaman audio dan wawancara digunakan untuk mengumpulkan data. Berdasarkan transkripsi, peneliti menganalisis interaksi bagaimana guru bereaksi terhadap respon siswa-siswa. Peneliti mengklasifikasikan reaksi – reaksi lisan guru tersebut ke dalam 14 fitur bahasa guru berdasarkan Walsh (2006) dan menemukan fitur yang membangun dan menghambat siswa untuk berbicara. Studi ini menemukan bahwa guru bereaksi terhadap respon siswa baik secara verbal maupun non-verbal. Guru menggunakan gerak tubuh, ekspresi wajah, kontak mata dan bahasa tubuh ketika melakukan reaksi non-verbal. Reaksi verbal guru dilakukan saat mengucapkan tanggapan guru. Ucapan guru tersebut diklasifikasikan ke dalam 14 fitur bahasa guru. Guru hanya menggunakan tujuh fitur bahasa guru dari empat belas, antara lain: Scaffolding, Referential Question, Extended Wait-Time, Extended Teacher Turn, Teacher Echo, Confirmation Checks, and Teacher Interruption. Dari tujuh fitur tersebut, satu - satunya fitur yang menghalangi siswa untuk berbicara yaitu Extended Wait-Time. Referential Question, Extended Teacher Turn dan Confirmation Checks membangun siswa untuk berbicara. Sedangkan sisanya, Scaffolding , Extended Teacher Turn dan Teacher Echo dapat membangun dan menghalangi siswa untuk berbicara. Dengan demikian dapat disimpulkan bahwa guru melakukan reaksi baik verbal dan non-verbal guru selama pelajaran. Guru hanya menggunakan tujuh fitur bahasa guru dari empat belas. Dari tujuh fitur, hanya Extended Wait-Time yang menghalangi siswa untuk pembicaraan. Sedangkan enam dari mereka dapat membangun dan menghalangi siswa untuk berbicara. Keywords : Classroom Interaction, Teacher Talk, Teacher Reaction, Features of Teacher Talk Abstract This is a descriptive qualitative study, which focused on the teacher’s reaction to the students’ responses and the construction or obstruction features of teacher talk. This study is aimed to describe the teacher’s reaction to the students’ responses and classified the verbal teacher’s reactions into 14 features of teacher talk based on Walsh (2006). The subjects of this research are a female English teacher and seventh graders of a Junior High School, At-Taqwa Surabaya. The main data was taken from the observation. The researcher used audio recording and interview to collect the data. The data were transcribed and analyzed qualitatively through certain steps then. The researcher classifies the verbal teacher’s reaction into 14 features of teacher talk based on Walsh (2006) and finds out the features which construct and obstruct the students to talk. This study found that the teacher conducted both verbal and non-verbal teacher’s reaction. The teacher used gestures, facial expression, eye contact and body language when conducting non-verbal teacher’s reaction. The verbal teacher’s reactions are conducted by uttering the teacher’s responses. Those teacher utterances are classified into 14 features of teacher talk then. The teacher used only seven features of teacher talk out of fourteen. They were Scaffolding, Referential Question, Extended Wait-Time, Extended Teacher Turn, Teacher Echo, Confirmation Checks, and Teacher Interruption. From those seven features, only Extended Wait-Time which obstructed the students to talk. Referential Question, Teacher Interruption, and Confirmation Checks constructed the students to talk. While, Scaffolding, Extended Teacher Turn and Teacher Echo constructed and obstructed the students to talk. It can be concluded that the teacher conducts both verbal and non-verbal teacher’s reaction during the lesson. From those seven features of teacher talk used, only Extended Wait Time, which obstructs the student to talk. While the other six features, both construct and obstruct the students to talk. Keywords : Classroom Interaction, Teacher Talk, Teacher Reaction, Features of Teacher Talk INTRODUCTION Teachers need an extra ability to teach English for Junior High School students since they are included in to young learners’ classification. Cameron (2001) defined young learners as those who are less than 14 years old. Unlike adult, young learners are generally conscript into language classes. They often have no obvious reason for learning English. Furthermore, young learners do not always have well developed literacy skills to support their learning English. They are not able to read or write in their own language. They often learn slowly and forget quickly since they are still developing cognitively, linguistically, socially, emotionally and physically. Musthafa (2010:123) mentioned that there are three reasons why teaching young learners becomes quite difficult. The first reason is the limited function in social interaction. The second reason is the short time in teaching English as a local content. The third reason is about teaching English for young learner needs to prepare good ability and good training for the teacher. The teachers need to be competence and confidence in practicing the language target, which is English. Besides, they must be active and creative in demonstrating the language accurately, clearly, fluently in order to scaffold the students in speaking English. The exposure toward English affects the successful of learning English. Hammer (2000:24) stated that, the language learners will be success if they are exposed to language, motivated to learn, and have opportunity to use the language they are learning. Hammer’s statement implies that to get the students succeed in learning English, the teacher should build the students’ exposure to English and give the students opportunities in using English. The teacher has to construct the students become active in the class. However, making the students active in speaking class becomes quite difficult. Most of them have much opinion, yet, they may feel unconfident even shy to speak up in English. Whereas, in the speaking class, the more practice is needed. Therefore, teachers should understand what languages would be more efficient to initiate talk and construct the students in participating and practicing English as the language target in order to create an environment in which the students feel more confident to speak English during the learning process. In a foreign language classroom, in this case an English class, the amount of student talk is expected to be higher than the teacher talk, especially in a speaking class. Walsh (2006) stated that all about language teachers use in order to control, organize, and motivate the class which cause interaction between teacher and students called teacher talk. The success of conducting teacher talk depends on the teacher’s strategies for managing interaction in the classroom. Some teachers give a change for the students to contribute and participate in learning process. According to Bailey (2003: 54 – 56), one of the four principles of teaching speaking is that the teacher should provide opportunities for the students to talk and limit his own talk. However, some teachers deny the students to participate in learning process. They obstruct the students when they seek to involve the lesson. Whereas, the high amount of student talk in the English classroom expands the students’ exposure toward English. Walsh (2002) examined the ways in which teachers construct or obstruct learner participation in classroom interaction, through their choice of language. Construction meant “increasing learning potential” which can be done through activities like, Direct Error Correction, Content Feedback, Checking for Confirmation, Extended Wait Time, and Scaffolding. Obstruction meant “reducing learning potential” which can be done through Turn Completion, Teacher Echo, and Teacher Interruptions. According to Walsh (2006) investigation about the 14 features of teacher talk that can construct and obstruct the students’ participating. The researcher wants to know whether the Walsh’s construction or obstruction of teacher talk are also be applied in Indonesia School contexts or not. This study outlines two research questions, “How does the teacher react to the students’ responses in order to initiate talk in the speaking class?” and “Which features of Teacher Talk do construct and obstruct the students to talk?” A point to be noted is that the way the teacher reacts to the students’ responses. The researcher makes detail about the description of teacher talk in the term of teacher’s reaction. The verbal teacher’s reactions are classified into 14 features of teacher talk based on Walsh (2006). METHODS This is descriptive qualitative study. The researcher describes the phenomenon happened which has no deal with number. McMillan (1992) explained that a qualitative research stresses on a phenomenological model or focuses on understanding and meaning which has no deal with number. The subjects of the study are a female English teacher and the seventh graders of Junior High School (SMP At-Taqwa Surabaya). The students consist of 38 students, 20 male and 18 female. While the teacher graduated from Surabaya State University in 2010. She has been teaching for 3 years: in MTs Miftahul Huda Pasuruan for a year and At- Taqwa for two years. The main data was taken through the observation. Audio recording and interview were used to collect the data. The data were then transcribed qualitatively. The researcher classified the verbal teacher’s reaction into 14 features of teacher talk based on Walsh (2006) and found out the features of teacher talk that construct and obstruct the students to talk. The researcher used tables to analyze the data. The tables contain of the analysis of teacher’s reaction, teacher talk and the result of interview between the researcher and the students. FINDINGS AND DISCUSSION Interaction has an important relation with communication; if there is no interaction, there cannot be communication (Thomas, 1987:4). Hence, interaction between the teacher and the student during the teaching learning process is needed, especially at the speaking class. There are four principles which need to be applied in teaching speaking (Bailey, 2003: 54 -56). One of them is the teacher should provide opportunities for students to talk and limit the teacher talk. This principle informs that the teacher should not dominate the talk and give the students more opportunity to talk. Rivers (1983:67) stated that to develop communication skill in a foreign language, the students must have continual practice in communicating. The teacher has to respond them back by giving reaction. The teacher’s reaction consists of verbal reaction, which is spoken and non-verbal reaction, which is unspoken such as gesture, touch, eye contact, hand coding, facial expression, body language and so on. The teacher’s utterances are included in the verbal teacher’s reaction. Those utterances can be classified into 14 features of teacher talk based on Walsh (2006). The researcher found that the teacher used seven features of teacher talk out of fourteen. From those seven features, only Extended Wait-Time which obstructed the student to talk. Referential Question, Teacher Interruption, and Confirmation Checks constructed the student to talk. While, Scaffolding, Extended Teacher Turn, Teacher Echo both constructed and obstructed the student talk. Walsh (2002) examined that construction can be done through activities like, Direct Error Correction, Content Feedback, Checking for Confirmation, Extended Wait Time and Scaffolding. While, obstruction can be done through Turn Completion, Teacher Echo, Teacher Interruptions. The first feature used was Scaffolding. This feature is divided into three categories, they are Reformulation Scaffolding, Extension Scaffolding, and Modeling Scaffolding. The researcher found those categories during the observation. The first feature, Reformulation Scaffolding, shows how the teacher reformulated the student’s utterance in order to make something clearer, for example: Extract 1: S6 : Why the cloth not not…ehm, you know? S9 : Yes, yes,, because usually indie clothing is like that and then they sell like, like jacket and, and, any other cloth but, but I can’t I can’t search it, search it.. T : Search to get the picture? S9 : Yes T : So, you mean that actually you sell many kind of cloths but, but, that is only the picture. Extract 1 shows the Reformulation Scaffolding used when the teacher repharaprased the student’s answer which was unclear. A student asked to her friend, then her friend answered it, however, the answer was unclear. The teacher repeated student’s answer by repharaprased it using her own words. According to the observation, this category constructs the students to talk. The second category is Extension Scaffolding. It showed when the teacher extended the the student’s contribution, for example: Extract 2: S8 : Eighty. T : Eighty. Eighty percent. Okay, sit with your group please. One, two, three.. Extract 2 shows that Extension Scaffolding occurred when the teacher extended the student’s answer. The student answered “eighty”, however, the teacher extended it by saying “Eighty percent”. This category obstructs the students to talk. The last category, modeling scaffolding, used to correct a student’s contribution by giving a model. According to the observation, this category obstructs the students to talk. Extract 3: S9 : Ustadzah, the event will start at 5 until 7 pm. What is the English of ‘akan diadakan’? T : Will be held. S9 : Held, okay. T : held, h-e-l-d (the teacher pronouns and spells it) Extract 3 shows the modeling scaffolding was used by the teacher when a student asked her the English of ‘akan diadakan’. The teacher answered it and modeled it by pronouncing that word. According to Flanders (1970), Scaffolding is included in the fourth category of indirect teacher talk. It provided how the teacher shows his or her agreement toward what the students are saying or doing by rephrasing the student’s idea. It is in the line with Nunan’s (1989) statements that the idea given by the student must be re-paraphrased or spoken differently. The second feature of teacher talk found was referential question. This feature is used to gain the students’ opinion by giving questions in which the teacher does not know the answer. This feature constructs the students to talk since it lets the students to deliver their own thought. Extract 4: S6 : What does it for? T : What do you think? S6 : Ehm, I think for what turn to get. Extract 4 shows the referential question used by the teacher. It showed when a student asked the teacher, and then the teacher answered it by giving the student a question “what do you think”. This question included referential question since it could gain the student ideas. It is important for the teacher to give some questions to the students in order to gain their opinion. Cazden (2001) stated that in classroom interaction, students are involved in two kinds of talks: 1). Talk with experts (teacher), usually the pattern is I-R-E (teacher question, student’s response and teacher evaluation); 2). Talk among peers. Therefore, it was important for teacher to give some questions in order to initiate talk which caused the students’ responses. The teacher used referential question to gain the students to deliver their opinion, their ideas and their thought. The third feature found was Extended Wait-Time. This feature used when the teacher gives the students sufficient time to respond or formulate the responses. According to the observation, this feature obstructs the student to talk. Extract 5: T : You’re welcome. Okay, girls, I give you time five minutes. I’m sorry, because Nabila uses my laptop, so you have to prepare with your laptop. Or one laptop, the other in the flashdisk, but you can use your friend’s laptop. The teacher asked the students to present their presentation in front of the class. However, they had not finished their presentation. Thus, the teacher gave five minutes more for the students to finish their presentation. Giving the students several times to respond or formulate on response is needed. The students are people who learn something. They need sufficient time in their learning process. Therefore, the teacher gave several times for students to answer a question given or finish their work. She gave sufficient times to the student to finish preparing their presentation. The fourth feature found was Extended Teacher-Turn. It is a feature, which gives the teacher time to deliver her contributions for more than one clause. The teacher needs time to explain the lesson. She used more than one clause while explaining the materials. Moreover, this feature could be used to command the students. This feature could construct the students to talk; yet, it could obstruct the students to talk sometimes. Extract 6: T : Okay, other question? Salma gets one point, do you want to keep it as yours or your group? If for your group please write down there 50. S6 : No no no. sorry friends. T : Okay, no other questions? No? S6 : Why the date is 7? From the Extract 6, it shows that the teacher used more than one clause. The teacher invited the students to ask some questions related to their friend’s presentation. In addition, she also commanded a student to write down the point she got because giving a question to her friend. However, this feature obstructs the student to talk, for example: Extract 7: T : Okay, prepare it well and finish your work and the one who is finish, you can give me the file. Prepare for your presentation ya, for your presentation girl. Extract 7 shows that the teacher spoke more than one sentence. However, there was no verbal response from the students. The teacher only commanded the students to prepare their presentations well and finish it. She also asked the student who has finished giving her file to the teacher. The fifth feature found was teacher echo. It shows the repetition of the teacher’s and the students’ utterance that is spoken by the teacher. Those repetitions were used to strengthen the contribution, which has given by the teacher or the student. Extract 8: (1) S4 : Lidya, T : Lidya, okay. Ksenia with? (2) S3 : Ninety. T : Ninety, okay, what about you, Michel? Those two dialogues above were the examples of teacher echo, which were found when the researcher conducted the observation. Both of them showed that the teacher repeated the student’s utterances before giving response to the student. In the first dialogue, the student said “Lidya”, and then the teacher repeated it by saying “Lidya” too before giving her next response, which was “okay. Ksenia with?”. In the line with the first dialogue, the teacher also repeated the student’s utterances by saying what the student has said. The student said “ninety” and the teacher repeated it. She said “ninety” first before giving her next response, which was “okay. What about you, Michell?”. According to Cullen (2002), repetition as a teaching strategy can be evident in both types of moves. Repetition is known as a teacher